Chemical and ecological state of the waters in the Novik Bay (Russky Island, Peter the Great Bay, Japan Sea) - Nadezhda K. Khristoforova; Yulia E. Degteva; Ksenia S. Berdasova; Alexander A. Emelyanov; Alexander Yu. Lazaryuk (Известия ТИНРО, 2016)
Chemical and ecological state of the Novik Bay waters is described on the data of surveys conducted in summer, autumn, winter, and spring of 2014-2015. Lowered content of dissolved oxygen is noted for summer, with occasional decreasing to 5-6 mg/L that is below the standard summer value for fishery ponds. However, the oxygen content restores quickly in autumn, up to 12 mg/L, that is conditioned by hydrodynamic activity, water temperature decreasing, and phytoplankton blooming. The latter process is confirmed by high values of BOD5 (4.44-5.58 mgO2/L) in autumn. Winter conditions under the sea ice are satisfactory for marine organisms: dissolved oxygen content is > 4 mg/L in the whole water column that is close to the standard winter value for fishery ponds.